Word power : phrasal verbs and compounds : a cognitive approach - Rudzka-Ostyn, Brygida (Berlin ; New York : Mouton de Gruyter, 2003)
Word Power: Phrasal Verbs and Compounds is a textbook for guided self-learning intended for post-intermediate and advanced learners of English. It contains some 1,100 phrasal compounds used with 17 particles/prepositions which combine with some 500 different verbs, nouns and adjectives. Numerous glosses allow the teacher to use it in very heterogeneous classes. Thanks to cognitive linguistics the material is organized around each particle giving the students an astonishing insight into the networks of metaphorical meanings of each particle. Furthermore, the book implements the most important f.
Frontmatter; Table of contents; Introduction: Words and the World; 1. OUT is leaving a container; 2. INis entering or being inside a container; 3. INTO is entering a container; 4. UPis positive verticality; 5. DOWN is negative verticality; 6. OFF is breaking contact; 7. AWAY is disappearing; 8. ON is contact; 9. OVER is higher than and close to; 10. BACK is returning; 11. ABOUT is dispersion; 12. (A)ROUND is vicinity or circular motion; 13. ABOUT/(A)ROUND is dispersion vs. circular motion; 14. ACROSS is motion to opposite side; 15. THROUGH is crossing a container; 16. BY is vicinity or path
Print version record.
eBooks on EBSCOhost
Keywords: English language -- Verb phrase; English language -- Textbooks for foreign speakers; Anglais (Langue) -- Syntagme verbal; Anglais (Langue) -- Manuels pour allophones; FOREIGN LANGUAGE STUDY -- English as a Second Language; English language; English language -- Verb phrase; Textbooks -- for foreign speakers